1993
DOI: 10.1063/1.110250
|View full text |Cite
|
Sign up to set email alerts
|

Surface passivation of GaAs using ArF excimer laser in a H2S gas ambient

Abstract: A dry surface passivation of GaAs using the combination of H2S gas with an ArF excimer laser was examined. Native oxides at the surface were etched away by laser irradiation in vacuum. By subsequent laser irradiation in a H2S gas ambient, the surface was covered with sulfur atoms. The dry passivation technique in this study is comparable to the wet passivation process using (NH4)2Sx treatment in terms of the sulfur coverage ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In the case of other III to V semiconductors, such as GaAs, laser processing in air can produce a time‐stable surface passivation . A GaAs surface cleaning by removing a low‐quality native oxide, followed by S passivation, by means of excimer laser irradiation has been also reported, showing in some cases an increase of the photoluminescence intensity …”
Section: Discussionmentioning
confidence: 98%
“…In the case of other III to V semiconductors, such as GaAs, laser processing in air can produce a time‐stable surface passivation . A GaAs surface cleaning by removing a low‐quality native oxide, followed by S passivation, by means of excimer laser irradiation has been also reported, showing in some cases an increase of the photoluminescence intensity …”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that irradiation of GaAs in air with 118 mJ/cm 2 XeCl and 75 mJ/cm 2 KrF lasers leads to the formation of a Ga x O y layer [12,13]. In vacuum, the efficient removal of carbon has been reported with a 53mJ/cm 2 pulse of an ArF laser irradiating GaAs, while over a thousand pulses were required to eliminate the Auger oxygen peak (originating from various surface oxides) under similar conditions of irradiation [14]. The removal of C and O from vacuum irradiated GaAs with 532 nm pulses has also been reported [15].…”
Section: Resultsmentioning
confidence: 98%
“…Photoassisted sulfur deposition has been examined using two S-containing precursors, H 2 S and elemental S. Both form sulfides under photon irradiation. On GaAs(100) c(8×2), Nooney et al found that, without photon assistance, only one monolayer of S could be built up by repeated cycles of H 2 S exposure at low temperature followed by heating to 600 K. When 193 nm photons were used, thicker and unsaturable sulfide layers were produced.…”
Section: 4 Nonthermal Surface Chemistry and Film Growthmentioning
confidence: 99%
“…Auger studies indicate that As remains below the GaS x layer up to 600 K. The authors propose that GaS and GaS 2 are both involved. However, on a different surface, GaAs(001), mainly AsS was formed after ArF excimer laser irradiation in an H 2 S ambient …”
Section: 4 Nonthermal Surface Chemistry and Film Growthmentioning
confidence: 99%
See 1 more Smart Citation